The Use of English Web Blog in Increasing Students’ Writing Skill at SMK Pemdes Ujungbatu - Sari, Raya Fitri; Syafi'i, M (State Islamic University of Sultan Syarif Kasim Riau, 2023)
The main objectives of this research were to find out whether there is significant difference of the students’ writing skill before being taught by using and after being taught using English Web Blog at SMK Pemdes Ujungbatu. The type of this research was pre experimental design. This research used one group pre-test and posttest design. The writer used one class as sample of the research by using purposive sampling in which the total sample was 18 students chosen from 5 classes as the population of this research. In collecting the data, this research used writing test. While, in analyzing the data, the writer used sample paired t-test as SPSS 25.0. The result of data analyzed showed that the mean score of the students after being taught by using English Web Blog (82.67) was higher that before being taught by using English Web Blog (74.33). It can be concluded that there was a significant difference on students’ writing skill of recount text before and after being taught by using English Web Blog at the tenth grade students of SMK Pemdes Ujungbatu.